Dynamic analysis and experiment of the seedling pick-up mechanism for pepper hole tray seedlings - Ren, Zhaoyang; Hu, Minjuan; Ji, Yao; Yan, Wei; Li, Kun; Zhou, Xunze; Zhang, Wenyi (International Journal of Agricultural and Biological Engineering, 2025)
To improve the quality of seedling picking and throwing in the mechanical transplanting process of pepper hole tray seedlings, this study establishes a dynamic model of pepper hole tray seedlings during the picking and throwing stages. Through analyses of the instantaneous force on stem during clamping, substrate force during pulling, and kinematic analysis during throwing, the relationships between stem deviation from cotyledon center and clamping height, picking mechanism rotation speed and clamp opening speed, as well as throwing speed, throwing height, and horizontal throwing displacement are obtained. The main influencing factors affecting throwing success rate and their critical values are determined, with the optimal clamping position found to be 15 mm from the surface of the substrate to the stem. Bench experiments explore the effects of picking mechanism rotation speed, throwing height, and planting mouth diameter on throwing success rate, with the critical ranges of each factor aligning closely with theoretical analysis results, validating the accuracy and feasibility of the model. To investigate the optimal combination of picking and planting mechanisms under conditions of high throwing rate, a response surface experiment analysis is conducted to establish regression mathematical models between major influencing factors and assessment indicators. Experimental results demonstrate that with mechanism rotation speed at 67 r/min, throwing height at 93 mm, and planting mouth diameter at 137 mm, the optimized throwing success rate reaches 94.58%. This study provides valuable insights for improving the throwing quality of pepper hole tray seedlings during transplanting. Keywords: seedling pick-up mechanism, plug seedlings, kinematic analysis, experimental design, critical conditions DOI: 10.25165/j.ijabe.20251801.9141 Citation: Ren Z Y, Hu M J, Ji Y, Yan W, Li K, Zhou X Z, et al. Dynamic analysis and experiment of the seedling pick-up mechanism for pepper hole tray seedlings. Int J Agric & Biol Eng, 2025; 18(1): 134–142.